Operational risk management and customer complaints: the role of product complexity as a moderator. - Abdul Rahim, Noor Fareen; Ahmed, Essia Ries; Sarkawi, Mohammad Nizam; Jaafar, Abdul Rahman; Shamsuddin, Jauriyah (Emerald Publishing Limited, 2019)
Purpose – The purpose of this paper is to examine the relationship between operational risk management and customer complaints. It also determines whether product complexity moderates the relationship between the operational risk management and customer complaints. Design/methodology/approach – This study utilizes a quantitative method: quantitative data were collected using a questionnaire. The population of this study is 1,845 local conventional bank branches based in Malaysia.Findings – The findings revealed that components of operational risk management, namely practice of hazard identification and formulation of implementation of risk control, have negative and significant relationships with customer complaints. Empirical evidence confirmed the moderating effects of product complexity on the relationship between operational risk management and customer complaints. Originality/value – From the perspective of developing countries, the main contribution of this study is the elucidation of the effect of operational risk management on customer complaints in commercial banks in Malaysia. This study confirmed the usability of the resource-based view theory in the banking industry, as well as operational risk management as a bank resource